(untitled) (Research, Society and Development, 2021)
Objectives: to identify nursing care after CPR resuscitation; produce a summary table of the main nursing care. Methodology: this is an integrative literature review carried out in the LILASCS, MEDLINE and BDENF databases. The time frame was the articles published in the last five years. The inclusion criteria were: articles dealing with the theme of cardiorespiratory arrest in emergency services, intensive care unit and semi-intensive care unit. Exclusion criteria were articles that address cardiorespiratory arrest in the mobile prehospital environment. Results: the care with preventive hypothermia, the record of care provided, strict control of vital signs and the assessment of metabolic disorder are configured as fundamental care provided by nurses. The information board characterized nursing care for patients in cardiorespiratory arrest, as a source of consultation. Conclusion: basic nursing care for patients in cardiac arrest were exposed in this research. The information board is configured as a source of consultation that will guide nursing care for patients after cardiac arrest.